Steerable chromatic dispersive metalenses in dual bands. (23rd June 2022) - Fu, Boyan; Li, Tianyue; Zou, Xiujuan; Ren, Jianzheng; Yuan, Quan; Wang, Shuming; Cao, Xun; Wang, Zhenlin; Zhu, Shining
Abstract: As a promising flat optical element, metasurfaces possess the powerful ability to manipulate chromatic dispersion, resulting in achromatic imaging, ultracompact spectrometers, and wavelength-dependent multifunctional nano-devices. However, conventional chromatic metalenses are incapable of arbitrarily tailoring dispersion within different bandwidths. Here, with a supercell composed of two nanostructures, we can arbitrarily control the chromatic dispersion of the metalens by using the phase differential equation and genetic optimization. We design three metalenses to verify the simultaneous tailoring of different chromatic dispersions in dual bands, which exhibits stronger chromatic dispersion manipulation capability compared with a single-structure-cell-based metalens. Our approach paves a new way for dispersion engineering of metalenses with potential applications in spectral imaging and material analysis.